Persepsi Nilai dan Kualitas Produk terhadap Keputusan Pembelian di Marketplace - Ibrahim, Darmawansah (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
This study aims to analyze the influence of perceived value and product quality on consumer purchase decisions in the marketplace. In today’s digital era, marketplaces have become one of the main platforms used by consumers for online shopping. Consumers not only consider price but also evaluate the benefits, quality, and value they perceive from the products offered. This research employs a quantitative approach using a survey method by distributing questionnaires to 100 marketplace users in Indonesia. The collected data were analyzed using multiple linear regression to determine the extent to which perceived value and product quality affect purchase decisions. The results show that both perceived value and product quality have a positive and significant effect on consumer purchase decisions. Consumers tend to be more confident in making a purchase when they feel they receive benefits that match the price paid and perceive the product as having good quality. These findings emphasize that marketing strategies in marketplaces should focus on enhancing the perceived value and maintaining consistent product quality to build consumer trust and encourage purchase decisions.